2004
DOI: 10.1108/09576060410513715
|View full text |Cite
|
Sign up to set email alerts
|

The perceived impact of JIT implementation on firms’ financial/growth performance

Abstract: This paper argues that solely depending on short-term financial performance indicators to justify the benefits of JIT implementation is very misleading and could harm a company's future long-term survival. The empirical study presented in this paper investigated the effect of (JIT) implementation on the use of operation performance measures. Furthermore, the effect of the JIT implementation and the use of the operating performance measures on firms' financial/growth performance, as perceived by the managers, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 6 publications
(8 reference statements)
6
53
0
5
Order By: Relevance
“…Productivity ratios using performance metrics, for example 'mean time between failures' and 'process yield percentage' (Lockamy III, 1998), though reflective of performance at the process or operations level, are not indicative of the performance at the firm level (Ahmad et al, 2004;Klingenberg et al, 2013). In essence scholars have argued for the holistic implementation of TQM across the firm in order to maximise and sustain benefits (Abdullah and Tari, 2012;Dhalgaard-Park et al, 2013).…”
Section: Quality Management Practices and Their Link To Performancementioning
confidence: 96%
See 1 more Smart Citation
“…Productivity ratios using performance metrics, for example 'mean time between failures' and 'process yield percentage' (Lockamy III, 1998), though reflective of performance at the process or operations level, are not indicative of the performance at the firm level (Ahmad et al, 2004;Klingenberg et al, 2013). In essence scholars have argued for the holistic implementation of TQM across the firm in order to maximise and sustain benefits (Abdullah and Tari, 2012;Dhalgaard-Park et al, 2013).…”
Section: Quality Management Practices and Their Link To Performancementioning
confidence: 96%
“…Direct and indirect effects of QM practices can be confounded by any number of variables such as marketing method and accounting practices (Ahmad et al, 2004;Fullerton et al, 2003;Klingenberg et al, 2013;York and Mire, 2004). Therefore, the use of oversimplified single constructs may not truly reflect the complex forces that influence cross-functional and cross-firm relationships with firm level performance and soft factors (Ahmad et al, 2004;Kaynak, 2003;Klingenberg et al, 2013). For example, Milgrom and Roberts (1990) suggest that it is not possible to isolate the effects of different QM implementations from the effectiveness of marketing campaigns when analysing financial performance.…”
Section: Quality Management Practices and Their Link To Performancementioning
confidence: 99%
“…Two of the most commonly used indicators in previous research were used to evaluate operational/non-financial (NFI) performance: delivery time and flexibility to change the product mix (e.g., Sim, 2001;Ahmad et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen studies in all have been found in the bibliography that use this indicator in the context of JIT (Sakakibara et al, 1997;Lieberman and Demeeter, 1999;Fullerton and McWatters, 2001;Fullerton and McWatters, 2002;Fullerton et al, 2003;Callen et al, 2003;Christiansen et al, 2003;Ahmad et al,2004;Cua et al,2001Cua et al, , 2006Ward and Zhou, 2006;Matsui, 2007;Bayo-Moriones et al, 2008;Inman et al, 2011;Danese et al, 2012).…”
Section: Kanban Systemmentioning
confidence: 99%
“…There is vast amount of technical and scientific work devoted to the analysis, assessment and design of production systems developed by several research Many of that research addresses the production systems from a management perspective and tries to understand the applicability and effectiveness of industrial practices and systems and develop the knowledge managers need to choose the solutions that better fit the needs of their organisations, as in Ahmad 2004. As another example, Chenall (1996 presents an empirical investigation that tries to establish links between organisational performance (expressed in terms of attributes such as delivery speed, scrap, rework and labour efficiency), and industrial management and engineering practices (namely technology policy, planning framework and product design infrastructure).…”
Section: Literature Reviewmentioning
confidence: 99%